Heat-shock protein vaccines as active immunotherapy against human gliomas. Issue 11 (November 2009) - Yang, Isaac; Han, Seunggu; Parsa, Andrew T
Modern advances in cancer immunotherapy have led to the development of active immunotherapy that utilizes tumor-associated antigens to induce a specific immune response against the tumor. Current methods of immunotherapy implementation are based on the principle that tumor-associated antigens are capable of being processed by antigen-presenting cells and inducing an activated cytotoxic T-lymphocyte-specific immune response that targets the tumor cells. Antigen internalization and processing by antigen-presenting cells, such as dendritic cells, or macrophages results in their surface association with MHC class I molecules, which can be recognized by an antigen-specific cytotoxic T-lymphocyte adaptive immune response. With the aim of augmenting current immunotherapeutic modalities, much effort has been directed towards enhancing antigen-presenting cell activation and optimizing the processing of tumor-associated antigens and major histocompatibility molecules. The goal of these immunotherapy modifications is to ultimately improve the adaptive specific immune response in killing of tumor cells while sparing normal tissues. Immunotherapy has been actively studied and applied in glioblastomas. Preclinical animal models have shown the feasibility of an active immunotherapy approach through the utilization of tumor vaccines, and recently several clinical studies have also been initiated. Recently, endogenous heat-shock proteins have been implicated in the mediation of both the adaptive and innate immune responses. They are now being investigated as a potential modality and adjuvant to immunotherapy, and they represent a promising novel treatment for human glioblastomas.